The Relationship Between the Use of Social Media and Deviant Sexual Behavior Among Adolescents: A Qualitative Study at SMA Negeri 3 Palu - Darwis, Lia; Suryani, Lili; Taqwin, Taqwin; Sumiaty, Sumiaty; Pont, Anna Veronica; Gusman, Gusman; Darwis, Enggar (Poltekkes Kemenkes Palu, 2025)
ABSTRACT Background: In the digital era, social media has become one of the most frequently used platforms among adolescents to interact, seek information, and access various types of content, including sexual content. This study aims to determine the relationship between social media use and sexual behavior among adolescents at SMA Negeri 3 Palu. Method: This study employed a quantitative approach with a cross-sectional design and involved 56 students selected using proportional random sampling. The research variables were social media use and adolescents’ sexual behavior. The research instrument was a questionnaire, and data were analyzed using the Chi-square test. Result: The findings revealed that 39 respondents (69.64%) were active social media users, and 24 respondents (61.5%) demonstrated deviant sexual behavior. The statistical test showed a p-value of 0.002 (<0.005). Conclusion: There was a significant relationship between social media use and deviant sexual behavior among adolescents. These findings highlight the importance of supervision and education regarding social media use among adolescents.